FMD outbreak in South Korea and its economic consequences - A. A. Funtikov; S. R. Kremenchugskaya (Ветеринария сегодня)
The paper presents OIE data on FMD outbreaks and assesses economic losses in the Republic of Korea in 2000, 2002, 2010 with a special attention given to the analysis of the FMD current epidemic situation on the Korean Peninsula in 2014-2016. The paper demonstrates the importance of FMD prevention, eradication, control in the countries of the Korean Peninsula and the Pacific Region.